1999
DOI: 10.1021/jp984341z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Hydrides on Hydrogen-Terminated Silicon (111)−(1×1) Surface

Abstract: X-ray photoelectron spectroscopy (XPS) and static secondary ion mass spectrometer (SSIMS) have been applied to characterize Si(111) surface treated with 40% NH4F solution. As-treated Si(111) surface is predominately terminated with monohydrides and free of contamination. The dynamics of etching process on ultra-clean atomically flat hydrogen-terminated Si(111) surface in 40% NH4F solution has been examined at various potentials including the open circuit potential (OCP) by using in situ electrochemical scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 24 publications
1
28
1
Order By: Relevance
“…12 It is generally accepted that H-terminated Si surfaces are fairly stable under atmospheric conditions and that monohydride (≡Si-H) terminated surfaces are more stable than di-or trihydride ()SiH 2 or -SiH 3 ) terminated ones due to smaller steric hindrance. 13,14 Niwano et al reported 15,16 that H-terminated Si(100) [hereafter abbreviated as H-Si(100)] surfaces were oxidized in back-bond by long-time (several-hundred hours) exposure to humid air. The back-bond oxidation of H-Si(100) and -(111) was also reported for several-minute immersion in 30% H 2 O 2 17 and for several-second immersion in aqueous 3% H 2 O 2 , 18 and even for immersion in pure water (containing dissolved air) for several hundred minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 It is generally accepted that H-terminated Si surfaces are fairly stable under atmospheric conditions and that monohydride (≡Si-H) terminated surfaces are more stable than di-or trihydride ()SiH 2 or -SiH 3 ) terminated ones due to smaller steric hindrance. 13,14 Niwano et al reported 15,16 that H-terminated Si(100) [hereafter abbreviated as H-Si(100)] surfaces were oxidized in back-bond by long-time (several-hundred hours) exposure to humid air. The back-bond oxidation of H-Si(100) and -(111) was also reported for several-minute immersion in 30% H 2 O 2 17 and for several-second immersion in aqueous 3% H 2 O 2 , 18 and even for immersion in pure water (containing dissolved air) for several hundred minutes.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well-known that Si surfaces etched with aqueous hydrogen fluoride (HF) are terminated mainly with hydrides (SiH n , n = 1, 2, or 3) and that successive etching with 40% ammonium fluoride (NH 4 F) produces atomically flat Si(111) surfaces terminated with monohydride (≡Si−H). Alkali etching under negatively applied biases produced similar atomically flat Si(111) surfaces . It is generally accepted that H-terminated Si surfaces are fairly stable under atmospheric conditions and that monohydride (≡Si−H) terminated surfaces are more stable than di- or trihydride (=SiH 2 or −SiH 3 ) terminated ones due to smaller steric hindrance. , …”
Section: Introductionmentioning
confidence: 99%
“…In the study of these site-specific chemical etching dynamics, the traditional chemical analysis method falls short due to the lack of sensitivity. Following the invention and widespread use of scanning probe microscopy (SPM), a different method, based on the study of surface morphology, has shown its unique strength in exploring the chemical dynamics. …”
Section: Introductionmentioning
confidence: 99%
“…Si (111) surfaces etched by 40% NH 4 F can be atomically smooth and a scanning probe microscope (SPM) can then be used to directly study the various surface sites and atomic configurations. Due to the slow etch rates while the surface is being etched, an STM can be used to image the surface in real time . On the basis of ex situ SPM studies, the mechanism of NH 4 -based etching of Si (111) has been explained as a competition between step-flow and surface-pit initiation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation